Assessment of renal fibrosis in murine diabetic nephropathy using quantitative magnetization transfer MRI. Issue 6 (30th May 2018) - Wang, Feng; Katagiri, Daisuke; Li, Ke; Takahashi, Keiko; Wang, Suwan; Nagasaka, Shinya; Li, Hua; Quarles, C. Chad; Zhang, Ming‐Zhi; Shimizu, Akira; Gore, John C.; Harris, Raymond C.; et al.
Abstract : Purpose: Renal fibrosis is a hallmark of progressive renal disease; however, current clinical tests are insufficient for assessing renal fibrosis. Here we evaluated the utility of quantitative magnetization transfer MRI in detecting renal fibrosis in a murine model of progressive diabetic nephropathy (DN). Methods: The db/db eNOS‐/‐ mice, a well‐recognized model of progressive DN, and normal wild‐type mice were imaged at 7T. The quantitative magnetization transfer data were collected in coronal plane using a 2D magnetization transfer prepared spoiled gradient echo sequence with a Gaussian‐shaped presaturation pulse. Parameters were derived using a two‐pool fitting model. A normal range of cortical pool size ratio (PSR) was defined as Mean±2SD of wild‐type kidneys ( N  = 20). The cortical regions whose PSR values exceeded this threshold (threshold PSR) were assessed. The correlations between the PSR‐based and histological (collagen IV or picrosirius red stain) fibrosis measurements were evaluated. Results: Compared with wild‐type mice, moderate increases in mean PSR values and scattered clusters of high PSR region were observed in cortex of DN mouse kidneys. Abnormally high PSR regions (% area) that were detected by the threshold PSR were significantly increased in renal cortexes of DN mice. These regions progressively increased on aging and highly correlated with histological fibrosis measures, while the mean PSR values correlated much less. Conclusion: Renal fibrosis in DN can be assessed by the quantitative magnetization transfer MRI and threshold analysis. This technique may be used as a novel imaging biomarker for DN and other renal diseases.